Persulphate-Co2+-Bisulphite Initiated Aqueous Polymerization of Acrylamide and Retardation by Organic Solvents - Bajpai, A.K.; Sharma, O.P. (Asian Journal of Chemistry, 2010)
The aqueous polymerization of acrylamide initiated by the persulphate metabisulphite redox couple and catalyzed by CO2+ ions has been iodometrically studied in atmospheric oxygen over the temperature range from 25º to 45 ± 0.2ºC. The effect of varying concentration of monomer, persulphate, bisulphite and CO2+ ions on the course of polymerization has been investigated. The following rate depgndence has been observed: Rp α [Monomer]1.0 [CO2+]1.0 [HSO:3–]0 [PS]1.0. Various inorganic salts and organic solvents were added to the reaction medium and the rate of polymerization was observed with a special emphasis on the retarding behaviour of organic solvents. The energy of activation was calculated to be 10.8 kcal/mol.